Research on drivers' visual characteristics in different curvatures and turning conditions of the extra-long urban underwater tunnels. (May 2020) - Jiao, Fangtong; Du, Zhigang; Wang, Shoushuo; Yang, Libo; Ni, Yudan
Highlights: With increase of radius, fixation distribution is wider, fixation time increases. With increase of radius, saccade angle is larger, range of its variation is wider. The driving situation is more stable than the left-turn when turning right. Special attention should be paid to small radius curve and long straight section. Abstract: In order to study driver's visual characteristics under different curvatures and turning conditions in extra-long urban underwater tunnels, fixation and saccade were herein regarded as the main research objectives. In this study, we carried out real vehicle testing on curved sections with 5 different radii and straight sections of the extra-long urban underwater tunnels. The driver's fixation characteristics were studied by using fixation distribution, fixation time, fixation frequency, fixation time ratio, and frequency ratio. The driver's saccade characteristics were investigated by selecting the saccade angle, saccade time, saccade frequency, saccade time ratio, and frequency ratio. Accordingly, mathematical models of the driver's fixation time, fixation frequency, saccade time, and saccade frequency under different curvatures and turning conditions in the extra-long urban underwater tunnel were established. Combined with the change of visual distance, sight distance, and sight zone, driver's visual characteristics in the extra-long urban underwater tunnel were further analyzed. The results demonstrated that the smaller the radius of the tunnel, the more focused driver's fixation time, the greater the psychological pressure, and the lower the safety when driving. Under the same radius, driver's tension and risk factors were higher during turning left, while driver's driving mentality was more relaxed and driving situation was further stable in the right-turn.